Implant Surface Design Regulates Mesenchymal Stem Cell Differentiation and Maturation. (March 2016) - Boyan, B.D.; Cheng, A.; Olivares-Navarrete, R.; Schwartz, Z.
Changes in dental implant materials, structural design, and surface properties can all affect biological response. While bulk properties are important for mechanical stability of the implant, surface design ultimately contributes to osseointegration. This article reviews the surface parameters of dental implant materials that contribute to improved cell response and osseointegration. In particular, we focus on how surface design affects mesenchymal cell response and differentiation into the osteoblast lineage. Surface roughness has been largely studied at the microscale, but recent studies have highlighted the importance of hierarchical micron/submicron/nanosurface roughness, as well as surface roughness in combination with surface wettability. Integrins are transmembrane receptors that recognize changes in the surface and mediate downstream signaling pathways. Specifically, the noncanonical Wnt5a pathway has been implicated in osteoblastic differentiation of cells on titanium implant surfaces. However, much remains to be elucidated. Only recently have studies been conducted on the differences in biological response to implants based on sex, age, and clinical factors; these all point toward differences that advocate for patient-specific implant design. Finally, challenges in implant surface characterization must be addressed to optimize and compare data across studies. An understanding of both the science and the biology of the materials is crucial for developing novel dental implant materials and surface modifications for improved osseointegration.